Antibacterial Activity of Scurrula ferruginea (Roxb. Ex Jack) Leaves Extract Against Staphylococcus aureus and Escherichia coli - Aditiyarini, Dwi; Sipayung, Nita Sonia; Prakasita, Vinsa Cantya (UIN Sunan Gunung Djati Bandung, 2024)
The mistletoe (Scurrula ferruginea) is a parasitic plant obtaining nutrients and water from host plants at Nglinggo tea plantation, Kulon Progo, Yogyakarta. Despite the numerous benefits of Scurrula ferruginea leaf, substantiation regarding its pharmacological activity is still lacking. Therefore, this research aimed to identify Scurrula ferruginea species and obtain secondary metabolites with antibacterial activity. The experiment was carried out by extracting Scurrula ferruginea leaf using maceration methods with 96% ethanol, followed by qualitatively and quantitatively phytochemical screening, inhibitory zone test, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) test. Several compounds, such as flavonoids, tannins, phenols, saponins, alkaloids, terpenoids, and steroids, were identified in the mistletoe extract. The results showed total flavonoid, phenolic, and tannin levels were 7.41 ± 0.38 mg QE/mg, 1672 ± 50.99 mg GAE/g, and 1.43 ± 0.15 mg TAE/g, respectively. Scurrula ferruginea leaf ethanolic extract showed the potential to form an inhibition zone against S. aureus in the moderate category at 525 mg/mL, but no significant activity was observed against E. coli. The MIC results of Scurrula ferruginea leaf ethanolic extract against S. aureus were 0.6%, and the MBC was at 2.4%. Furthermore, the MIC value against E. coli was 14%, and the MBC value was 28%. Based on these results, it could be concluded that Scurrula ferruginea leaf ethanolic extract showed high effectiveness in inhibiting and killing S. aureus bacteria compared to E. coli, with MIC and MBC values of 0.6% and 2.4%, respectively